2014
DOI: 10.1096/fj.13-245654
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity‐induced mitochondrial dysfunction in rat cerebral arteries

Abstract: Exposure to microgravity results in cardiovascular deconditioning, and cerebrovascular oxidative stress injury has been suggested to occur. To elucidate the mechanism for this condition, we investigated whether simulated microgravity induces mitochondrial dysfunction in rat arteries. Four-week hindlimb unweighting (HU) was used to simulate microgravity in rats. Mitochondrial reactive oxygen species (ROS), mitochondrial membrane potential (Δψm), mitochondrial permeability transition pore (mPTP) opening, mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…3a, b, c). However, it is still equivocal whether PTP opening is a consequence or a cause of increasing ROS generation, since elevated ROS generation would lead to PTP opening [43,44] and VDAC1-dependent mitochondrial permeability transition (MPT) also engaged a positive feedback loop promoting ROS generation [58]. In addition to that, our study showed that significant differences of all events including [Ca 2? ]…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…3a, b, c). However, it is still equivocal whether PTP opening is a consequence or a cause of increasing ROS generation, since elevated ROS generation would lead to PTP opening [43,44] and VDAC1-dependent mitochondrial permeability transition (MPT) also engaged a positive feedback loop promoting ROS generation [58]. In addition to that, our study showed that significant differences of all events including [Ca 2? ]…”
Section: Discussionmentioning
confidence: 59%
“…Alterations in oxidative state are usually associated with the loss of mDW [43][44][45]. Therefore, a subsequent study was undertaken to investigate the relationship between the ALA-SDT-induced oxidative stress and changes of mitochondria membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…), the expression of cleaved caspase‐3 and cleaved caspase‐9, markers of apoptosis, were also found to be significantly increased in ISO‐treated cardiomyocytes. Coincidently, simulated microgravity resulted in cerebrovascular mitochondrial dysfunction, and crosstalk between NOX and mitochondria participated in the process [Zhang et al, ]. Together, these data support an essential role of nuclear calpain‐2 in the regulation of the mitochondrial machinery through modulating Bcl‐2 levels.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study examining organelle function in cardiomyocytes in simulated microgravity also showed an upregulation in genes and proteins associated with microchondrial processes as well as down-regulation of cytoplasmic translational mechanisms, including ribosomes and endoplasmic reticulum65. As mitochondria have been shown to be highly susceptible to stress-related damage and dysfunction in simulated microgravity66, the upregulation of light organ transcripts associated with these processes may be a mechanism for the host squid to maintain mitochondrial and other organelle homeostasis to help regulate cellular redox control during microgravity conditions, regardless of the symbiotic state of the host.…”
Section: Discussionmentioning
confidence: 98%